PENGARUH MOTIVASI DAN TIM KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN SOPPENG - Andi Adawiyah; Bahariah (AkMen JURNAL ILMIAH, 2023)
This research was conducted at the Education and Culture Office of Soppeng Regency, located on Jl. Salotungo Watansoppeng. The population in this study were all employees of the Soppeng Regency Education and Culture Office. The sample was determined using the Saturated Sampling technique, so the number of samples in this study was 45 respondents. To determine the effect of motivation and team work on employee performance, multiple linear regression analysis is used. Based on the results of the regression analysis, it can be concluded that motivation influences employee performance at the Soppeng Regency Education and Culture Office. The work team influences the performance of employees at the Education and Culture Office of Soppeng Regency, the variable motivation has the most dominant effect on employee performance at the Education and Culture Office of Soppeng Regency Based on the results of the research, the author suggests that the Soppeng Regency Education and Culture Office. to motivate employees by fulfilling all the needs of employees so that employee performance will increase. To the Department of Education and Culture of Soppeng Regency. to pay more attention to the work team being implemented, whether it is effective or not, so that the implementation of the work team is effective